Comprehensive Characterization of Extractable Phenolic Compounds by UPLC-PDA-ESI-QqQ of Buddleja scordioides Plants Elicited with Salicylic Acid - J. O. Díaz-Rivas; R. F. González-Laredo; J. A. Chávez-Simental; J. B. Montoya-Ayón; M. R. Moreno-Jiménez; J. A. Gallegos-Infante; N. E. Rocha-Guzmán (Journal of Chemistry)
Buddleja scordioides has a rich phytochemical composition and reported medicinal properties. An increase in its secondary metabolites production could improve its functional properties. A strategy to enhance its biological potential is to subject the plant to elicitation with phytohormones such as salicylic acid under controlled environmental conditions. The present study explores the effect of exogenous application of three salicylic acid levels as elicitation treatment in B. scordioides plants. Phenolic profile, enzymatic activities, and antioxidant capacity were evaluated. Elicitation with 100 µM of salicylic acid resulted in the biosynthesis of phenolic compounds with recognized biological activity.